Da aparência de crítica ao silenciamento: Veja e o discurso sobre o fracasso educacional. - Orsatto, Franciele Luzia de Oliveira (2009)
The present work aims to analyze, based on the French Discourse Analysis approach, the representation of Brazilian education constructed by Veja magazine, in the section called Ponto de Vista. Veja was chosen because it is a representative magazine in the Brazilian, as well as in the world publishing market: Veja is the most read magazine in the country and the fourth information magazine most sold in the world. Due to the magazine s privileged position, what is published becomes an authorized discourse, as if it were involved by a veracity aura . Through informative and opinion texts, the magazine doesn t express how Brazilian education and teachers are, but it makes it happen. While Veja talks about relevant topics related to the country, like education, the magazine puts itself in the important place as an opinion former, able to significantly influence the people to adopt an attitude. With this power reaffirmed all the time, Veja is capable of constructing representations and stereotypes, which, many times, are accepted by the readers, who read the text disarmed . To analyze the way this process occurs, two opinion texts that talk about Brazilian education were chosen. The purpose is to investigate the effects of meaning, relating the language with its exteriority, and based on that, to verify the stereotypes that are supported. The concept of discursive formation, combined with concepts of subject and ideology are going to be used in the analysis, which is based on studies of Pêcheux (1997), Maingueneau (1993) and Orlandi (2001). To investigate the representation constructed by the mass media about educational issues is the first step to think about education s images and the reasons that lead Journalism and public opinion to support these images. To focus on the symbolic fights that happen on the journalist method is a way to try to understand the complex interpretation word game and ideology reflexes; it is also a tool to better understand the organization of social structures, of institutions and, finally, of the supplies and its relation with the symbolic.